Pengaruh Kontribusi Sektor Pertanian, Indeks Pembangunan Manusia, dan Investasi Terhadao Tingkat Kemiskinan di Provinsi Bali - Suka Prameswari, Kadek Putri; Purbadharmaja, Ida Bagus Putu (OIKOS: Jurnal Kajian Pendidikan Ekonomi dan Ilmu Ekonomi, 2024)
Poverty constitutes a crucial challenge encountered by Indonesia, including Bali Province, potentially impeding economic growth and national development. Poverty can be defined as a condition wherein individuals face difficulties in fulfilling daily needs, encompassing both primary and secondary necessities. This study aims to evaluate the impact of the agricultural sector, Human Development Index (HDI), and investment on the poverty levels in Bali Province. The research encompasses all administrative regions within Bali Province over the period 2010-2022, utilizing secondary data. The methodology employed is panel data regression analysis. The findings indicate that the contribution of the agricultural sector partially exerts a positive and significant effect on poverty levels. In contrast, the HDI variable exhibits a negative and significant influence on poverty levels, as determined through partial analysis. Furthermore, investment does not demonstrate a significant impact on poverty levels. The study concludes that an increase in the agricultural sector's contribution tends to elevate poverty levels in Bali Province. Conversely, enhancements in the HDI significantly contribute to reducing poverty levels in Bali Province.